Six-week inhalation of lead oxide nanoparticles in mice affects antioxidant defense, immune response, kidneys, intestine and bones. Issue 2 (12th January 2022) - Tulinska, Jana; Krivosikova, Zora; Liskova, Aurelia; Lehotska Mikusova, Miroslava; Masanova, Vlasta; Rollerova, Eva; Stefikova, Kornelia; Wsolova, Ladislava; Babelova, Andrea; Tothova, Lubomira; Busova, Milena; Babickova, Janka; et al.
Abstract : Inhalation of PbO nanoparticles in mice has adverse effects on immune response, oxidative stress, antioxidative defense, kidneys, intestine and bones. Abstract : Due to widespread use in various industrial processes, the risk of inhalation exposure to lead oxide nanoparticles (PbO NPs) is growing and limited information evokes the need for assessment of hazard to human health. The aim of our work was to evaluate the effects of PbO NPs on blood, immune response, kidneys, intestine, and bones in mice exposed to 121.7 μg PbO per m 3 continuously for 6 weeks. Immune assays showed significantly increased phagocytic activity of granulocytes, stimulated proliferative activity of spleen lymphocytes, a higher percentage of spleen CD3 − CD335 + and thymus CD3 + CD8 + cells, and moderately increased proinflammatory cytokines in the PbO NP-exposed group. Analysis of blood antioxidant defense revealed a significantly lower GSH concentration and a decrease in the GSH/GSSG ratio due to PbO NP inhalation. Markers of oxidative stress (AGEs and AOPP) in the intestine, but not in the kidneys, were significantly increased. In the kidney of PbO NP-treated mice, we found elevated expression of proinflammatory factors (TNF-α, IL-6, iNOS, and Xdh) and IL-10 and upregulated expression of F4/80 (mature macrophage marker). Moreover, increased expression of pro-fibrotic markers (TGFβ2, type I and type III collagen) was detected. Massive accumulation of Pb together with a significant decrease of Ca, P, and Mg concentrations in the tibia were accompanied by a nonsignificant increase in bone mineral density. Our findings indicate adverse effects of sub-chronic inhalation of PbO NPs, manifested as undesired stimulation of the immune system, oxidative stress in the intestine, inflammation, and pro-fibrotic response in the kidneys and massive accumulation of Pb in bones.